Accessibility of cooling centers to heat-vulnerable populations in New York State. (September 2019) - Nayak, Seema G.; Shrestha, Srishti; Sheridan, Scott C.; Hsu, Wan-Hsiang; Muscatiello, Neil A.; Pantea, Cristian I.; Ross, Zev; Kinney, Patrick L.; Zdeb, Michael; Hwang, Syni-An A.; Lin, Shao
Abstract: Introduction: Spending a few hours to cool down in a cooling center reduces the impact of heat on health. But limited or lack of accessibility of these facilities is often a barrier to their utilization. The objective of this study was to assess accessibility of the cooling centers to heat-vulnerable populations in New York State (NYS) by various modes of transportation. Methods: We estimate the proximity of 377 cooling centers to general and heat-vulnerable populations in NYS (excluding New York City (NYC)) and determine their accessibility via walking, public transportation and driving. Distances between tract populations and nearest cooling center, and between cooling centers and public transportation stops were estimated. Accessibility in four metropolitan regions was determined via public transportation while accessibility in heat-vulnerable rural areas was estimated via driving. Results: Distances to nearest cooling center ranged from 0 to 53.2 miles with only a third of NYS population within walking distance (0.5 miles) of a cooling center. About 51% of heat-vulnerable tracts were within 0.5 miles, with an average distance of 2.4 miles to the nearest cooling center. Within the four metro politan regions 80% of cooling centers within 0.5 miles of a public transportation stop. All cooling centers in heat-vulnerable tracts were accessible via public transportation. In rural heat-vulnerable tracts, driving distances averaged at about 18 miles. Conclusions: In urban areas many residents were not within walking distance of a cooling center, but most, and nearly all in the most heat-vulnerable areas, were within walking distance of public transportation to a cooling center. In rural locations distances were longer, and accessibility is a greater issue. Cooling centers can be a valuable resource for general and heat-vulnerable populations during an extreme heat event. When planning and implementing cooling centers, it is therefore important to improve accessibility and address other barriers that can hamper their utilization. Highlights: One-third of NYS population is within walking distance of a cooling center. In the metro politan areas, public transportation improved accessibility of cooling centers. All cooling centers in heat-vulnerable areas were accessible via public transit. In rural areas, cooling centers were fewer and distances longer. Free and accessible transportation can improve cooling center utilization.